Effects of Early Maturation on Growth, Fertility and Testosterone Levels in Broiler Breeder Males - Pietsch, C.; Oates, S.; Hess, J.; Berry, W. (International Journal of Poultry Science, 2008)
A study was conducted determine the feasibility of rearing broiler breeder males to an earlier age of sexual maturation. Three hundred Ross males were divided at 3 weeks of age into three treatments and four reps. Control birds (CD) were fed a normal 15% grower diet and an increased photoperiod began at 22 weeks of age. The fast growth (FG) birds were divided into 2 treatments; high protein (HP) birds were fed a 20% grower diet and normal protein (NP) birds were fed the control diet. FG males were raised to the breeder guideline recommend 22 wk target body weight by the age of 16 weeks, at which time photoperiod was increased to promote sexual maturity. CD males were photostimulated (PS) at 22 weeks. The second part of the trial was a fertility study. Following PS, 16 cockerels from each treatment were divided into 2 replicates and placed with 80 hens/ replicate. Eggs were collected and set weekly to determine fertility. Results indicated no differences between the NP and CD birds in performance. NP males performed better with respect to uniformity and growth. The HP males had the lowest fertility but the highest uniformity. It was concluded that early maturation is feasible in male broiler breeders and extra protein is unnecessary for an accelerated growth program.